Academic library outreach program: case study of the Institute of Teacher Education (IPG) in the state of Kedah / Nur Amira Eliana Abd Halim and Roziya Bt Abu. - Abd Halim, Nur Amira Eliana; Abu, Roziya (Universiti Teknologi MARA Cawangan Selangor, 2017)
The notion of an academic library outreach program denotes the efforts uphold by an institution’s academic library to serve their academic community, namely; students, academician, researchers and non-academic administrators. However, the theory and the practices of an outreach program in a Malaysian academic library and Malaysian public library tends to be overlapping. The aim of this article is to discover and deliberate on the factors that affect an outreach program in an academic library. In doing so, study result from two Institutes of Teacher Education (IPG) in the State of Kedah is selected. This study adopts a qualitative case study approach with in-depth individual interviews of the leading librarian for each institution, and later the thematic content analysis and cross-case analysis is used throughout this study in order to analyze the data. From the result of the interviews in the two Institutes of Teacher Education (IPG) in the State of Kedah, two most important factors emerge and it is said to be the key factor the affect an academic library outreach programs. This paper is approached from the leading of librarian’s perspective for each institution, namely; CS1 and CS2.